2003
DOI: 10.1523/jneurosci.23-23-08330.2003
|View full text |Cite
|
Sign up to set email alerts
|

Complex Formation between the Postsynaptic Scaffolding Protein Gephyrin, Profilin, and Mena: A Possible Link to the Microfilament System

Abstract: Gephyrin is an essential component of the postsynaptic cortical protein network of inhibitory synapses. Gephyrin-based scaffolds participate in the assembly as well as the dynamics of receptor clusters by connecting the cytoplasmic domains of glycine and GABA(A) receptor polypeptides to two cytoskeletal systems, microtubules and microfilaments. Although there is evidence for a physical linkage between gephyrin and microtubules, the interaction between gephyrin and microfilaments is not well understood so far. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
110
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 116 publications
(118 citation statements)
references
References 42 publications
2
110
2
Order By: Relevance
“…75,[82][83][84] Profilin and Mena A study seeking the linkage between gephyrin and microfilament identified profilin, Mena and G-actin as gephyrin-binding proteins. 85 Endogenous profilin and Mena were found to colocalize with gephyrin in the inhibitory synapses of spinal cord neurons, and were enriched in gephyrin-rich domains of the neuronal plasma membrane. 85 Gephyrin and profilin 1 were shown to form a complex, 86 but via an unexpected binding mode that required the E domain of gephyrin and the actin/ PIP 2 -binding site of profilins (Giesemann et al, 85 but also see Bausen et al 87 ).…”
Section: Collybistinmentioning
confidence: 98%
See 1 more Smart Citation
“…75,[82][83][84] Profilin and Mena A study seeking the linkage between gephyrin and microfilament identified profilin, Mena and G-actin as gephyrin-binding proteins. 85 Endogenous profilin and Mena were found to colocalize with gephyrin in the inhibitory synapses of spinal cord neurons, and were enriched in gephyrin-rich domains of the neuronal plasma membrane. 85 Gephyrin and profilin 1 were shown to form a complex, 86 but via an unexpected binding mode that required the E domain of gephyrin and the actin/ PIP 2 -binding site of profilins (Giesemann et al, 85 but also see Bausen et al 87 ).…”
Section: Collybistinmentioning
confidence: 98%
“…85 Endogenous profilin and Mena were found to colocalize with gephyrin in the inhibitory synapses of spinal cord neurons, and were enriched in gephyrin-rich domains of the neuronal plasma membrane. 85 Gephyrin and profilin 1 were shown to form a complex, 86 but via an unexpected binding mode that required the E domain of gephyrin and the actin/ PIP 2 -binding site of profilins (Giesemann et al, 85 but also see Bausen et al 87 ). A study examining the potential impact of these multipartite interactions on the function of gephyrin showed that cytochalasin D (an actin-depolymerizing agent) had differential effects on gephyrin clusters that were lost following cytochalasin D treatment of immature cultures but not following the same treatment of more mature cultures.…”
Section: Collybistinmentioning
confidence: 98%
“…Gephyrin is composed of an N-terminal domain (GephG, residues 1-181) and a C-terminal domain (GephE, residues 318-736), which are connected by an unstructured linker (residues 182-317). Gephyrin was discovered 6 by co-purification with glycine receptors (GlyRs) and found to be responsible for anchoring and accumulating GlyRs at postsynaptic sites, which is accomplished by the simultaneous binding of gephyrin to the GlyR b subunit [7][8][9][10] and elements of the cytoskeleton 11,12 . A number of gene knockout studies have addressed the role of the gephyrin-GABA A R interaction in vivo.…”
mentioning
confidence: 99%
“…So far no direct interaction with microfilaments has been demonstrated, but pharmacological studies indicate a function of actin filaments in determining the cluster size (12). Therefore, it is not surprising that binding of gephyrin to key regulators of microfilament dynamics such as profilin I, neuronal profilin IIa, and microfilament adaptors of the Mena/VASP family including neuronal Mena has been reported recently (13). The binding site of gephyrin on GlyR has been mapped to a stretch of 18 amino acids located within the large cytoplasmic loop connecting transmembrane helices three and four of the GlyR ␤-subunit (GlyR␤-loop) (14), but the binding site on gephyrin is not known.…”
mentioning
confidence: 99%